Arbitrary detentions continue in Venezuela - Amnesty International (Amnesty International, 2023)
Venezuela: Arbitrary detentions continue as a tool of government control and repression. In the new report, Life detained: Politically motivated arbitrary detentions continue in Venezuela Amnesty International denounces the Nicolás Maduro.
Keywords: 2023-08 August